دور مناهج الدراسية فى تأصيل الوعى السياحى والبيئى - عبداللطيف، علاء الدين أسامة; موسى، سید علي; عيد، نيفين جلال إبراهيم; منصور، سعاد عمران Mansour, Suad Emran (جامعة قناة السويس - كلية السياحة والفنادق, 2007)
نشر الوعى السياحي والبيئي والعمل على تنميته لدى جميع أفراد المجتمع أصبح ضرورة ملحة لتنشيط الحركة السياحية القادمة لمصر ولتعميق التأثيرات الإيجابية لهذا النشاط , لأن الوعى السياحى والبيئى هما القاعدة الأساسية التى يجب أن ترتكز عليهما التنمية السياحية الناجحة , وحيث أن المدرسة هى مؤسسة رسمية من مؤسسات التنشئة الاجتماعية تهدف إلى إعداد أفراد المجتمع للحياة والإسهام الفعال فى تقدم مجتمعهم فقد وقع الاختبار على المنهج المدرسى كوسيلة فعالة من وسائل تنمية الوعى السياحى والبيئى. Spreading tourism and environment awareness and exerting an effort to develop them among the people has become a vital necessity for activating and promoting the tourism movement coming to Egypt and for deepening and enhancing the positive effects of this activity. As the school is the formal institution that aims at preparing the members of society for life and the effective contribution to the progress of their society ' the researchers have chosen the scholastic curricula as an effective means for developing tourism and environment awareness therefore this research aims are Employing all the elements of the curriculum (content - procedures - learning activities and assessment) in developing the tourism and environment awareness with its general concept, and Focusing on the points of strength and weakness in some of the secondary stage lessons with all its specializations that can be employed in developing tourism and environment. The obtained results shaved that The spread of educational and cultural illiteracy is one of the main reasons of several social problems, especially the development of tourism and environment awareness. on the basis of the study recommended are: the insert on of topics with cultural depth that deal with local and international tourism in the scholastic curricula, increasing the volume of the environment topics in the different scholastic curricula of the main subjects.
Keywords: الوعى البيئى; السياحة; الوعى السياحى